ANALISIS PEREMAJAAN KWH METER PRABAYAR TERHADAP KEANDALAN SISTEM TENAGA LISTRIK - Mhd Idris; Zuraidah Tharo; Parlin Siagian (CV. Hawari, 2025)
Measuring and Limiting Devices (APP) or kWh meters have a very significant role in securing PT.PLN (Persero) income. kWh Meter acts as a transaction point between PT.PLN (Persero) as a producer and customers as consumers, therefore the accuracy of the kWh Meter in measuring energy consumption used by customers plays an important role as company income, because from all PT.PLN (Persero) business processes from generation, transmission, to distribution, only energy measured in the customer's kWh Meter will be the electricity bill that must be paid by the customer as a consumer to PT.PLN (Persero) as a producer. To obtain real measurement results with good quality, consistent preparation and evaluation are needed in its implementation, if not implemented properly it will result in losses for the company in the form of losses caused by the kWh Meter being jammed or damaged and still installed at the customer's transaction point. Therefore, APP must be managed properly and correctly by competent and highly dedicated officers. APP maintenance is carried out with the aim of avoiding measurement discrepancies by APP which ultimately cause excess or shortage of bills.